2014
DOI: 10.1016/j.jfoodeng.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

An apparatus for partial ice-melting to improve yield in progressive freeze-concentration

Abstract: a b s t r a c tA small test apparatus was made for partial melting of ice at controlled conditions in temperature and stirring speed. Ice cubes from 10 wt% sucrose were partially melted in this apparatus at 4 temperature and 4 stirring speeds. At the lower temperature with relatively faster stirring speed, the initially-melted fractions effectively contained the higher concentration of solute than the later-melted fractions. The partial ice-melting technique was combined with progressive freeze-concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…By this system, 12.18L of the apple juice was concentrated, in about 2 hr's operation time, to 3.50L with concentration increased from 13.7 to 25.5 o Brix with a yield of 63.8%. In this case, the yield may not be satisfactory but this could be improved to the necessary level by applying the partial ice-melting technique (Miyawaki et al, 2012;Gunathilake et al, 2014b).…”
Section: Progressive Freeze-concentration Of Apple Juicementioning
confidence: 99%
“…By this system, 12.18L of the apple juice was concentrated, in about 2 hr's operation time, to 3.50L with concentration increased from 13.7 to 25.5 o Brix with a yield of 63.8%. In this case, the yield may not be satisfactory but this could be improved to the necessary level by applying the partial ice-melting technique (Miyawaki et al, 2012;Gunathilake et al, 2014b).…”
Section: Progressive Freeze-concentration Of Apple Juicementioning
confidence: 99%
“…As a result, this method requires a very complicated system as described before, which in turn makes the SC process as the most expensive separation method among the other concentration enhancement methods (Miyawaki et al, 2012;Gunathilake et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this drawback, the application of partial ice-melting (PIM) in Fig. 14 to the ice formed after PFC was proved to be effective to improve yields in the process (Miyawaki et al, 2012;Gunathilake et al, 2014b), and an integrated system of PFC combined with PIM was established as shown in Fig. 19 (Miyawaki et al, 2016b).…”
Section: Freezing and Freeze Concentrationmentioning
confidence: 99%